New Mexico Poetry Renaissance - Niederman, Sharon; Sagan, Miriam; Creeley, Robert (Red Crane Books Santa Fe, 1994)
In La Opera, Leroy Quintana writes: "When Roberto's mother asked / him if he liked the opera / he, of course, said, si / because he truly does, / (particularly Puccini), / and she immediately, / said she did not, that / when la Operah came on / at four with her chisme / she immediately switches / to some other channel."
At the Cave Mouth -- after the siege of Leningrad -- The Mesa We Climbed / Lucile Adler -- El Gato / Jimmy Santiago Baca -- Chinese Space -- Sphericity / Mei-Mei Berssenbrugge -- I Saw Kit Carson Still Alive -- This Language Isn't Speech -- From Himal Journal / John Brandi -- Poems from Memory's Village / Alvaro Cardona-Hine -- You Are Real as Earth, y Mas -- You First -- The Road to Zacapo / Ana Castillo -- Legana of Lace -- Mercado Day -- Artery of Land / Denise Chavez -- I am still as stone -- Climbing -- Returning to Taos, after many seasons / Judson Crews -- To Live with the Beloved -- Winter Solstice / Victor Di Suvero -- The High Road to Taos / Martin Edmunds -- White Panther -- Salmon in the Pool -- Stanford Street Poem -- Saturn Is Mostly Weather / Gene Frumkin -- Fin de la Fiesta -- Leaving the Vigil Studio / Greg Glazner -- The House That Makes It So -- Human Non-Sequitur -- All of Love / Larry Goodell -- Silent Dialogue -- Two Floating Shapes -- The Final X / Renee Gregorio -- Promise -- The Myth of Blackbirds -- The Place the Musician Became a Bear / Joy Harjo -- Juniper -- The Old Ways / Gerald Hausman -- Grist for Grace -- Samurai Angels -- (A Dream of Frida) / Judyth Hill -- Haiku Series -- Mission Ruins / Elizabeth Searle Lamb -- Weaving Cave -- Frijoles Canyon / Donald Levering -- In a child's memory -- January 30th, 1989 -- Feast Day Preparation -- February 3rd, an excerpt / Harold Littlebird -- High School Graduation Pantoum -- Something Like Marriage -- Something -- The Angels of Pittsburgh / Joan Logghe -- Good God Gertie You're Cool -- 1st of May -- Easter Bread -- New Year's Eve at Hot Springs Ranch / Anne MacNaughton -- Rolling through the Country of Nouns -- Bent's Fort (in English and Spanish) -- Bar Chinere / E.A. Mares -- Only Say the Word: A Poem for Three Women's Voices (an excerpt) / Demetria Martinez -- Desert Stones Talking -- Reading Braille -- Things My Mother Must Have Said / Mary McGinnis -- Beads of Rain -- Our New Life -- Summer Sublet / Carol Moldaw -- Sittings for Whitman -- Camp Robbers -- Cundiyo Willows / Linda Monacelli-Johnson -- When Mud Woman Begins -- There Is Nothing Like an Idea -- The Living Exhibit under the Museum's Portal -- Towa -- One Adobe at a Time / Nora Naranjo-Morse -- A Story of How a Wall Stands / Simon J. Ortiz -- From Chaco Body: I. Transparency -- From Chaco Body: II. Already Gone -- From Chaco Mind: II. The Music of Time / V.B. Price -- La Opera -- Blue -- Poem for Grandmother / Leroy Quintana -- Retablos for Frida -- Mirrors -- Your Scissored Rooms of Memory -- Dancing with the Doe / Margaret Randall -- Weaving the Rain -- What Was There To Do on the Plains -- Marilyn Monroe Indian -- Desert Nights / Leo Romero -- Shell in the Desert -- Hotel Flora -- Passover -- The Lonesome Death of Federico Garcia Lorca / Miriam Sagan -- For Earaches -- Para dolor de los oidos -- For Toothaches -- Para dolor de muelas / Jim Sagel -- The New World -- Guatemalan Worry Dolls -- Returning Home / Rebecca Seiferle -- Precious -- Incarnation / Joseph Somoza -- The Flower Path -- Original Memory -- Whiteout -- From the Rooftop / Arthur Sze -- Green Tara -- Waking -- The Wheel -- The Continental Divide / Anne Valley-Fox -- Sipapu: The Core -- River Girl -- Portrait -- The Encircled Grove / Keith Wilson -- Walking, of Course.
Includes bibliographical references.
67182
Keywords: American Poetry -- New Mexico; American Poetry -- 20th Century; New Mexico -- Poetry